DESIGN AND DEVELOPMENT 2D GAME “PERANG GERILYA JENDERAL SUDIRMAN” USING GAME DEVELOPMENT LIFE CYCLE METHOD - Diny Anggriani Adnas; River River (Universitas Internasional Batam, 2022)
Video games is used mostly for entertainment, but video games also can be used for learning it can make the player follow a story while playing. Indonesian have many history and heroic story however many Indonesian people already forgotten what is tfhe hero do on history of Indonesian to deserve claim a title of Indonesian hero, so because of that author produce a game that tell everyone one of Indonesian history and heroic story named “Perang Gerilya Jenderal Sudirman” that can help to remind them. This story is about Indonesian Hero General Sudirman and the unity of Indonesian people to fight back against enemy Holland. This game is created using unity and C# Programming Language. Unity is a game engine that help developer to create the game and for C# is for developer to create function or logic for the game. This Research using GDLC (Game Development Life Cycle) Method. GDLC is a method process stages of game development that consists initiation, pre-production, production, testing, beta, release. By Creating this game the author hope this game can be release and help the people intends to learn the history and heroic story of General Sudirman and the unity of Indonesian people fighting the invader through game.